Direct acceleration of an annular attosecond electron slice driven by near-infrared Laguerre–Gaussian laser. (26th May 2021) - Jiang, C.; Wang, W. P.; Weber, S.; Dong, H.; Leng, Y. X.; Li, R. X.; Xu, Z. Z.
Abstract: A new near-infrared direct acceleration mechanism driven by Laguerre–Gaussian laser is proposed to stably accelerate and concentrate electron slice both in longitudinal and transversal directions in vacuum. Three-dimensional simulations show that a 2-μm circularly polarized LG_p^l ( p = 0, l = 1, σ z = −1) laser can directly manipulate attosecond electron slices in additional dimensions (angular directions) and give them annular structures and angular momentums. These annular vortex attosecond electron slices are expected to have some novel applications such as in the collimation of antiprotons in conventional linear accelerators, edge-enhancement electron imaging, structured X-ray generation, and analysis and manipulation of nanomaterials.